Analysis of Wall Climbing Extracurricular Management (Artificial Rock Climbing) at Mahira Alam School, Kota Bengkulu - Muhammad Edo Trioka; Martiani Martiani; Azizatul Banat (Sinar Sport Journal, 2021)
This study aims to: 1) analyze the management of extracurricular wall climbing (artificial rock climbing) at the Alam MAHIRA school in Bengkulu City. 2) analyze the planning of extracurricular wall climbing (artificial rock climbing) management at the MAHIRA Nature School, Bengkulu City. 3) analyze the organization in the management of extracurricular wall climbing (artificial rock climbing) at the MAHIRA Nature School, Bengkulu City. 4) analyzing the implementation in the management of extracurricular wall climbing (artificial rock climbing) at the MAHIRA Nature School Bengkulu City. 5) analyzing supervision in the management of extracurricular wall climbing (artificial rock climbing) at the MAHIRA Nature School, Bengkulu City. This research method uses a qualitative descriptive method. Descriptive research is aimed at finding the elements, characteristics, characteristics of a phenomenon. The subjects in this study involved the principal, student representatives, wall climbing trainers (artificial rock climbing), wall climbing athletes (artificial rock climbing) at the MAHIRA Natural School Bengkulu City. The data sources to be used are primary data and secondary data. Primary data is the result of informal interviews while secondary data is in the form of documents and observations. Data collection techniques used in this study using observation techniques, interviews, documentation. From the results of the analysis, it was found that from meetings 1-8, it was concluded that the results of the observation of wall climbing extracurricular activities (artificial rock climbing) at the MAHIRA Nature School Bengkulu City had been carried out very well.